2008
DOI: 10.1007/s10806-008-9129-2
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Choice and Ethical Dilemmas in Land Management: Environmental Quality and Food Safety in California Agriculture

Abstract: As environmental and conservation efforts increasingly turn towards agricultural landscapes, it is important to understand how land management decisions are made by agricultural producers. While previous studies have explored producer decision-making, many fail to recognize the importance of external structural influences. This paper uses a case study to explore how consolidated markets and increasing corporate power in the food system can constrain producer choice and create ethical dilemmas over land managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 37 publications
0
61
0
1
Order By: Relevance
“…Control efforts that potentially reduce biodiversity, such as noncrop vegetation clearing and indiscriminate poison baiting, may increase fecal shedding potentially through promotion of intraspecific transmission of pathogens. In a study carried out by Stuart,88.9% of crop growers in the Salinas Valley region that were interviewed indicated that they had taken at least one measure to actively discourage or eliminate wildlife, with bare ground buffers and poisoned stations being used by more than one-half of the respondents (11). The challenge still remains as to how we can enhance preharvest food safety while promoting environmentally sustainable farm practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control efforts that potentially reduce biodiversity, such as noncrop vegetation clearing and indiscriminate poison baiting, may increase fecal shedding potentially through promotion of intraspecific transmission of pathogens. In a study carried out by Stuart,88.9% of crop growers in the Salinas Valley region that were interviewed indicated that they had taken at least one measure to actively discourage or eliminate wildlife, with bare ground buffers and poisoned stations being used by more than one-half of the respondents (11). The challenge still remains as to how we can enhance preharvest food safety while promoting environmentally sustainable farm practices.…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife have been implicated in outbreaks involving foodborne pathogens (8)(9)(10), which has prompted growers in California to implement stringent wildlife intrusion control measures, such as fencing, poison baiting, and clearing of noncrop vegetation in areas adjacent to produce fields (11). The role of various small mammal species as potential reservoirs of deleterious pathogens, such as Salmonella and E. coli O157:H7, however, still remains uncertain.…”
mentioning
confidence: 99%
“…Further, emerging evidence suggests that removal of non-crop vegetation fails to reduce, and may even increase, pathogen prevalence on leafy-green vegetable farms in the California Central Coast , while degrading important ecosystem benefits such as natural pest control services (Letourneau et al 2015, Karp et al 2016). Removing vegetation is expensive and at times conflicts with landowners' acknowledged environmental stewardship responsibilities (Crohn and Bianchi 2008;Gennet et al 2013;Hardesty and Kusunose 2009;Stuart 2009). Furthermore, such approaches may conflict with California's regulatory targets for surface water quality.…”
mentioning
confidence: 99%
“…Pathways to agroecological management through mediated markets in Santa Catarina, Brazil 2005;Stuart, 2008), articulates how decision-making results from a defined relationship between individual agency and structural constraints, such as cultural, socialinstitutional and economic forces that mediate the range of options available to individuals. For example, economic constraints to the adoption of agroecological practices include increased costs or labour requirements (Darnhofer et al, 2005), the risk of decreased yields (Rodriguez et al, 2009), and lack of access to credit (Defrancesco et al, 2008;Falconer, 2000).…”
Section: Policy Bridgementioning
confidence: 99%